Corporate communication worldwide : an introduction - Herlé, Mariët, ....-; Rustema Carin, ....- (Groningen : Noordhoff, 2012)
Corporate Communication Worldwide covers a wide range of corporate communication aspects and prepares those who aim to be active in the communication field in an international context. In today's world, the meaning of worldwide is truly dynamic and this book reflects such new reality. By covering some of the basic principles of global media theory, intercultural communication, internal communication and marketing communication, the authors prepare you for a true understanding of the international communication practice. Special attention is given to global case studies from all the continents in the world, including some of the emerging markets like China, Brazil, India, Russia and South Africa. The different cases, practical examples and tips given by the authors to the reader offer a first and clear understanding of what to expect in the communication profession. Both undergraduate and graduate students or young professionals who would like to be introduced in this professional field, can use this textbook.
1. the communication of organisations - 2. global aspects of corporate communication - 3. communication theory - 4. corporate communication - 5. marketing communication - 6. internal communication - 7. strategy and planning - 8. organisation of communication - 9. media and other tools -
Op de voorkant: an introduction
Bevat: literatuurlijst
Keywords: Bedrijfscommunicatie; Bedrijfsimago; Go international; International office